Dietary Polyphenol and Methylsulfonylmethane Supplementation Improves Immune, DAMP Signaling, and Inflammatory Responses During Recovery From All-Out Running Efforts - McFarlin, Brian K.; Hill, David W.; Vingren, Jakob L.; Curtis, John H.; Tanner, Elizabeth A. (Frontiers in Physiology, 2021)
Nutritional ingredients with defined mechanisms of action can be useful in the recovery of the body from the physical demands of a habitual training plan. The purpose of this study was to determine the effect of dietary supplementation with optimized curcumin, pomegranate ellagitannins, and MSM (R + MSM) on immune-associated mRNA during early recovery (i.e., up to 8 h post-exercise) following all-out running efforts (5-km, 10-km, and 21.1-km). Subjects (N = 14) were randomized to either a supplement (R + MSM) or a control group using an open label design. The study was completed over a period of 31-day prior to a scheduled half-marathon race. Venous blood samples were collected into PAXgene tubes at baseline, subsequent samples were collected at 2, 4, and 8 h after each running effort. A 574-plex mRNA Immunology Array (NanoString) was measured for each sample and ROSALIND® Advanced Analysis Software was used to examined changes in 31 annotated immune response pathways and specific mRNA changes. The greatest change in immune pathways occurred at 2 h (GSS > 3) followed by 4 h (GSS 2–3) and 8 h (GSS 1–2). R + MSM was associated with an increase in innate immunity (CAMP, LTF, TIRAP, CR1, IL1R1, CXCR1, PDCDILG2, and GNLY) and a blunted/smaller increase in damage-associated molecular pattern (DAMP) signaling/inflammation (TLR4, TLR5, S100A8, S100A9, and IFP35). We also found changes in immune-associated mRNA that have not been previously linked to exercise recovery (SOCS1, SOCS2, MME, CECAM6, MX1, IL-1R2, KLRD1, KLRK1, and LAMP3). Collectively these results demonstrate that supplementation with a combination of optimized curcumin, pomegranate ellagitannins, and methylsulfonylmethane resulted in changes that may improve biological recovery from all-out running efforts.